Skandinaviske lærebøker i leksikografi og leksikologi –tverrnasjonalt oversyn og vurdering - Vikør, Lars S. (Nordiske Studier i Leksikografi, 2006)
Scandinavian introductory books on lexicography and lexicology – a comparative survey and an assessment. This article gives a brief survey of Scandinavian (Danish, Norwegian and Swedish) introductory books on lexicology and lexicography. Seven books are discussed one by one, and a comparison is done as to which sectors within the field are covered in the three countries.